Dispensing with Age? Marriage Dispensation, Household Resilience, and the Tensions Between Islamic and State Law - Khafid, Muhamad; Ash Shabah, Musyaffa Amin; Hamid, Nor 'Adha Ab (Sakina: Journal of Family Studies, 2025)
Although Law No. 16 of 2019 stipulates a minimum marriage age of 19, marriage dispensation requests remain prevalent in Bekasi, highlighting a persistent gap between legal regulation and social practice. This study examines the judicial considerations underlying the granting of marriage dispensation in the Bekasi Religious Court, applying an empirical case study approach supported by literature review and document analysis. The principles of al-Maqashid al-Khamsah were employed to evaluate the judges’ reasoning. The findings reveal that the dispensation was granted primarily due to the close relationship between the petitioner and the respondent, alongside parental concerns regarding potential adverse consequences if the request was denied. The decision was legally grounded in Articles 8–10 of the Marriage Law and Articles 39–43 of the Compilation of Islamic Law, which permit marriage despite non-compliance with the statutory age requirement. However, such dispensations carry potential risks for marital stability, particularly in psychological, social, and economic domains. This study contributes to the discourse on judicial discretion by demonstrating how al-Maqashid al-Khamsah can serve as a normative framework for balancing legal, religious, and social considerations. It underscores the necessity for judges to weigh not only immediate familial concerns but also the long-term resilience of households, thereby ensuring that judicial decisions safeguard the welfare of couples and future generations.